CHARACTERZING THE USE OF PALLIATIVE DRUGS ON 57 CANCER PATIENTS, AT DATEH DISTRICT HEALTH CENTER, LAMDONG PROVINCE - Do Van Mai; Bui Tung Hiep; Bui Dang Minh Tri; Vo Quang Trung; LeThi Quy Thao; Dang Van Hoang (Tạp chí Y học Quân sự, 2023)
Purpose: We aimed to characterize the use of palliative drugs in cancer patients, treated at the Dateh District Medical Center, Lamdong province. In order to further clarify the effect of drugs in palliative treatment for cancer patients. Methods: Retrospective, cross-sectional descriptive study. Results: The proportion of patients using palliative drugs from the time of admission to the end of the study: 3rd class analgesics increased from 42.11% to 71.93%; 1st class analgesics decreased from 28.07% to 12.28%, and 2nd from 36.84% to 15.79%. The majority of patients used 2 drugs (54.39%), followed by 1 drug (24.56%) and 3 drugs (21.05%). The dosage of palliative drugs used is within the recommended limits. Drug route: at the time of admission, the majority of patients used drugs orally (50.88%), followed by intramuscular injection (31.58%), intravenous infusion (15.79%) and penetrates through the skin (1.75%). At the end of the study, the majority of patients received the drug intramuscularly (49.12%), followed by intravenous infusion (24.56%) and oral (22.81%).